Active Wrinkles to Drive Self-Cleaning: A Strategy for Anti-Thrombotic Surfaces for Vascular Grafts - Cerda-Villablanca, E (Elsevier Ltd, 2019)
The inner surfaces of arteries and veins are naturally anti-thrombogenic, whereas synthetic materials placed in blood contact commonly experience thrombotic deposition that can lead to device failure or clinical complications. Presented here is a bioinspired strategy for self-cleaning anti-thrombotic surfaces using actuating surface topography. As a first test, wrinkled polydimethylsiloxane planar surfaces are constructed that can repeatedly transition between smooth and wrinkled states. When placed in contact with blood, these surfaces display markedly less platelet deposition than control samples. Second, for the specific application of prosthetic vascular grafts, the potential of using pulse pressure, i.e. the continual variation of blood pressure between systole and diastole, to drive topographic actuation was investigated. Soft cylindrical tubes with a luminal surface that transitioned between smooth and wrinkled states were constructed. Upon exposure to blood under continual pressure pulsation, these cylindrical tubes also showed reduced platelet deposition versus control samples under the same fluctuating pressure conditions. In both planar and cylindrical cases, significant reductions in thrombotic deposition were observed, even when the wrinkles had wavelengths of several tens of μm, far larger than individual platelets. We speculate that the observed thrombo-resistance behavior is attributable to a biofilm delamination process in which the bending energy within the biofilm overcomes interfacial adhesion. This novel strategy to reduce thrombotic deposition may be applicable to several types of medical devices placed into the circulatory system, particularly vascular grafts. © 2018 Elsevier Ltd